Analisis Pengaruh Kemampuan Kerja, Kesempatan Berkinerja, Motivasi Kerja, Iklim Organisasi, dan Budaya Organisasi terhadap Kinerja Karyawan Perusahaan Manufaktur di Kab. Mojokerto - Ludi Wishnu Wardana (Jurnal Aplikasi Manajemen, 2012)
Research focuses on employees’s performance at manufacturer’s industries in Kab. Mojokerto, and aimed to investigate work abilities analysis, opportunity to perform, motivation of work, organization climate and organizational culture of employees’ performance at manufacturer’s industries in Kab. Mojokerto. The population are employees of middle/large manufacture’s industries in Kab. Mojokerto which have totally of 167 industries and 33.440 employees. Technical data analysis use SEM (Structural Equation Modelling) with AMOS program (Analisis of Moment Structure) Ver 4.01. Result shows that: 1) work abilities has positively interactive and significantly toward opportunity to perform, 2) work abilities has positively interactive and significantly toward motivation of work, 3) work abilities has positively interactive and significantly toward employees’ performance, 4) opportunity to perform has positively interactive and significantly toward motivation of work, 5) opportunity to perform has positively interactive and significantly toward employees’ performance, 6) organization culture has positively interactive and significantly toward motivation of work, 7) organization culture has not positively interactive and significantly toward employees’ performance, 8) organization climate has positively interactive and significantly toward motivation of work, 9) organization climate has positively interactive and significantly toward employees’ performance, 10) motivation of work has positively interactive and significantly toward employees’ performance.Keywords: Work Abilities, Organization Culture, Organization Climate, Opportunity to Perform, Motivation of Work Employees’ Performance.